Long-Term Evolution of Highly-Elliptical Orbits: Luni-Solar Perturbation Effects for Stability and Re-entry - Colombo, Camilla (Frontiers in Astronomy and Space Sciences, 2019)
This paper investigates the long-term evolution of spacecraft in Highly Elliptical Orbits (HEOs). The single averaged disturbing potential due to luni-solar perturbations, zonal harmonics of the Earth gravity field is written in mean Keplerian elements. The double averaged potential is also derived in the Earth-centered equatorial system. Maps of long-term orbit evolution are constructed by measuring the maximum variation of the orbit eccentricity to identify conditions for quasi-frozen, long-lived libration orbits or initial orbit conditions that naturally evolve toward re-entry in the Earth’s atmosphere. The behavior of these long-term orbit maps is studied for increasing values of the initial orbit inclination and anomaly of the perigee with respect to the Moon’s orbital plane. In addition, to allow meeting specific mission constraints, quasi-frozen orbits can be selected as graveyard orbits for the end-of-life of HEO missions. On the opposite side, unstable conditions can be exploited to target Earth re-entry at the end-of-mission.